Using Artificial Intelligence NLP Model To Improve EFL Highschool Students’ English Speaking Ability - Irsan Suandi Idrus; Arqam Arqam; Magdahalena Tjalla; Abdul Haris Sunubi; Ambo Dalle (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The study focused on improving students’ speaking skills through the use of AI-based Natural Language Processing (NLP) tools. The main goals are to find and analyze the using Artificial Intelligence NLP models in improving English speaking ability among students at MAN 2 Parepare, and to know and analyze what factors influence the success of using Artificial Intelligence NLP models in enhancing the English-speaking ability of EFL students at MAN 2 Parepare. This study applied a descriptive quantitative method, collecting data from 34 students using observation, oral tests, and questionnaires. The oral tests evaluated fluency, pronunciation, accuracy, and content, while the questionnaire—based on the Technology Acceptance Model (TAM)—measured students’ perceptions of the tool’s usefulness and ease of use. The results showed three main findings. First, the use of AI NLP models like Google Assistant offered personalized and interactive speaking practice, which helped improve students’ speaking performance. Second, there was a significant difference between pre-test and post-test results, with the t-test score (2,316) being higher than the t-table value (1,697), showing the positive impact of the AI tool. Third, two key factors supported the success of this approach: 74,19% of students considered the AI tool “very useful,” and 70,97% found it “very easy to use.” These factors contributed to increased motivation and active participation in speaking activities.